Benthic foraminifera as tracers of brine production in the Storfjorden "sea ice factory" - Fossile, Eleonora; Nardelli, Maria Pia; Jouini, Arbia; Lansard, Bruno; Pusceddu, Antonio; Moccia, Davide; Michel, Elisabeth; Peron, Olivier; Howa, Hélène; Mojtahid, Meryem (Biogeosciences, 2020)
International audience The rapid response of benthic foraminifera to environmental factors (e.g. organic matter quality and quantity, salinity, pH) and their high fossilisation potential make them promising bio-indicators for the intensity and recurrence of brine formation in Arctic seas. Such an approach, however, requires a thorough knowledge of their modern ecology in such extreme settings. To this aim, seven stations along a north–south transect across the Storfjorden (Svalbard archipelago) have been sampled using an interface multicorer. This fjord is an area of intense sea ice formation characterised by the production of brine-enriched shelf waters (BSW) as a result of a recurrent latent-heat polynya. Living (rose bengal-stained) foraminiferal assemblages were analysed together with geochemical and sedimentological parameters in the top 5 cm of the sediment. Three major biozones were distinguished. (i) The “inner fjord” zone, dominated by typical glacier proximal calcareous species, which opportunistically respond to fresh organic matter inputs. (ii) The “deep basins and sill” zone, characterised by glacier distal agglutinated fauna; these are either dominant because of the mostly refractory nature of organic matter and/or the brine persistence that hampers the growth of calcareous species and/or causes their dissolution. (iii) The “outer fjord” zone, characterised by typical North Atlantic species due to the intrusion of the North Atlantic water in the Storfjordrenna. The stressful conditions present in the deep basins and sill (i.e. acidic waters and low food quality) result in a high agglutinated ∕ calcareous ratio (A∕C). This supports the potential use of the A∕C ratio as a proxy for brine persistence and overflow in Storfjorden